A Novel Thermal-Visual Place Learning Paradigm for Honeybees (Apis mellifera) - Scheiner, Ricarda; Frantzmann, Felix; Jäger, Maria; Mitesser, Oliver; Helfrich-Förster, Charlotte; Pauls, Dennis (Frontiers in Behavioral Neuroscience, 2020)
Honeybees have fascinating navigational skills and learning capabilities in the field. To decipher the mechanisms underlying place learning in honeybees, we need paradigms to study place learning of individual honeybees under controlled laboratory conditions. Here, we present a novel visual place learning arena for honeybees which relies on high temperatures as aversive stimuli. Honeybees learn to locate a safe spot in an unpleasantly warm arena, relying on a visual panorama. Bees can solve this task very well at a temperature of 46°C, while at temperatures above 48 °C bees die quickly. This new paradigm, which is based on a pioneering work in Drosophila, allows us now to investigate thermal-visual place learning of individual honeybees in the laboratory, for example after controlled genetic knockout or pharmacological intervention.